Acute toxicity study morpholinium 2-[5-(pyridin-4-yl)-1,2,4- triazol-3-ylthio] acetate in white mice - Bushueva, I. V.; Knysh, E. G.; Panasenko, A. I.; Бушуєва, Інна Володимирівна; Панасенко, Олександр Іванович; Книш, Євгеній Григорович (Канада : Shiny World Corporation, 2014)
Creation of new low-emission and high domestic drugs with a wide spectrum of biological activity, which could compete with expensive imported drugs - one of the urgent tasks of pharmaceutical science. A key step in creating original drugs is directed synthesis of biologically active substances with pronounced pharmacological effect and low toxicity. Analysis of scientific literature over the last decade has shown that a great opportunity to create new and effective drug substances have heterocyclic compounds, in particular, derivatives of 1,2,4-triazole. Of particular interest is the morpholinium 2-[5-(pyridin-4-yl)-1,2,4-triazol-3-ylthio] acetate, as a substance with high pharmacological activity. Accordingly, the search for biologically active substances of 1,2,4-triazole, is relevant, has theoretical and practical significance. In the course of the study found that the investigated substance belong to the class of low-toxic or non-toxic compounds.
Keywords: morpholinium 2-[5-(pyridin-4-yl)-1,2,4-triazol-3-ylthio] acetate; acute toxicity; parameters of acute toxicity